THE APPLICATION OF MATHEMATICAL METHODS IN THE THEORY OF FUZZY SETS IN MODELING DECISION-MAKING IN THE ECONOMIC AND LEGAL DEVELOPMENTS - Andrey N. Vaschekin (Статистика и экономика)
Mathematical models that reflect the fuzzy nature of the interaction of various actors in the economy and law, allow us to solve by similar methods such problems as exploring potential partners based on the interaction of consignment contracts, long-term range calculation of wholesale companies, warehouse operations modeling, pricing, optimization of transportation, bills of exchange schemes, consistency, expert estimates in the process of codification and consolidation of the Legislation.